The Effect of Mathematical Dakon Media on the Multiplication Operation Ability of Whole Numbers in Grade 4 Madrasah Ibtidaiyah Students - Adwitiya, Salsabila; Usodo, Budi; Yamtinah, Sri (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
The low understanding of Grade 4 students at Madrasah Ibtidaiyah regarding multiplication operations with whole numbers is one of the main obstacles in mathematics learning that must be addressed promptly. This study aims to determine the effect of using dakon mathematics media on multiplication operation ability and to enhance the effectiveness of mathematics learning among Grade 4 MI students. The method used is quantitative with a quasi-experimental approach and a pretest-posttest control group design. The research sample consisted of two classes: the experimental class used dakon media, while the control class used conventional methods, with 20 students in each class.The data collection technique in this study was carried out using pretests and posttests to measure students' multiplication ability before and after treatment. The data analysis technique used was quantitative statistical analysis with a t-test to examine the difference in average multiplication ability between the experimental and control classes.The results of the study showed a significant increase in multiplication operation skills in students who used dakon media compared to those who did not use the media . The dakon media proved effective in helping students understand the concept of multiplication through a concrete and enjoyable approach. Thus, the use of dakon mathematics media has a positive impact on improving multiplication skills in Grade 4 Madrasah Ibtidaiyah students.